Estimating Cotton Yield: SS-AGR-450/AG450, 03/2021 - Mulvaney, Michael J.; Brooks, Emma; Devkota, Pratap; Carter, Ethan; Broughton, De; Mauldin, Mark; Iboyi, Joseph; Bashyal, Mahesh; Wright, David; Small, Ian (EDIS, 2021)
Preharvest estimation of cotton yield can help growers to determine their return on investment, assess weather-related damages, and adjust crop management. This publication outlines the steps to calculate a reliable estimate of cotton yield. Written by Michael J. Mulvaney, Emma Brooks, Pratap Devkota, Ethan Carter, De Broughton, Mark Mauldin, Joseph Iboyi, Mahesh Bashyal, David Wright, and Ian Small, and published by the UF/IFAS Agronomy Department, March 2021.